Espanhol como língua de herança: um estudo das crenças e atitudes linguísticas - Ramos, Quézia Cavalheiro Mingorance (2020)
The border areas between Brazil and other South American countries house an enormous linguistic diversity, resulting from the contact between Portuguese and Spanish, indigenous and immigrant languages, such as the dialects of German, Italian, among others. The objective of this dissertation is to identify the linguistic beliefs and attitudes of eight Brazilians, children of a mother and/or father whose mother tongue is Spanish, in relation to their heritage language. This objective was woven with the purpose of investigating the beliefs and attitudes generated in a situation of languages and cultures in contact, that is, in plurilingual environments. To this end, we rely on the dialogues built between Sociolinguistics, Ethnolinguistics, since the relationship between language and society is explored, and Social Psychology, which contributes especially to theoretical discussions about beliefs and attitudes. The methodological procedures used throughout the research included (i) semi-structured interviews, based on a script of semi-open and exploratory questions; (ii) audio recording of the reports made, with a view to qualitative analysis. The basic theoretical assumptions for research include discussions about migratory movements in Brazil (PATARRA; BAENINGER, 2004); formation of multilingual scenarios (CALVET, 2009); bilingualism (MACKEY, 1962; MAHER, 2007; GROSJEAN, 2010); heritage language (VALDÉS, 2000; VAN DEUSEN-SCOLL, 2003; POLINSKY, 2018; MORONI, 2017); identity(ies) (HALL, 2006) and beliefs and attitudes (LAMBERT; LAMBERT, 1975; MORENO FERNÁNDEZ, 2009). The analysis of the reports was based essentially on the mentalist approach, which comprises the attitude from three components - the affective, the cognitive and the conative. The analysis of the corpus shows (a) beliefs and attitudes towards the language of inheritance, as well as the culture of inheritance; (b) multiple identities constructed, in view of the influence of the cultures involved; (c) the influence of the role of the parents, considering that it may be an interethnic couple or not, in the transmission of the heritage language and culture. It is important to emphasize that we hope, through the reflections brought, to contribute to the deconstruction of stigmas in environments of linguistic-cultural contact, with the valuation of plurilingual environments and the transmission of heritage languages, as well as to the elaboration of linguistic policies in the country.